The role of Torremolinos in the queer history of Spain: New narratives beyond Madrid and Barcelona - Cuevas-del-Barrio, Javier (My University, 2022)
The progress in recent decades in the achievement of civil rights within the LGTB community in Spain (decriminalization of homosexuality, equal marriage, Trans law) has led to a review of the role that different organizations and cities (Barcelona, Madrid) have played in the achievement of these rights. 2017 marked the 40th anniversary of the first demonstration for LGBT rights in Barcelona (June 1977), organized to demand the repeal of the Ley de Peligrosidad (dangerousness law) passed during the Franco dictatorship. That demonstration had replicas a year later in cities such as Madrid, Bilbao and Seville and, at the end of that year, the withdrawal of homosexuality from the dangerousness law was achieved. 2018 marked the 40th anniversary of these demonstrations, ephemeris that continued in 2019 with the celebration of the fiftieth anniversary of the Stonewall Inn riots in New York (USA) which, historically, has meant the beginning of the homosexual liberation movements. These commemorations were accompanied by a process of revision of the role that cities such as Barcelona or Madrid had played in this journey. However, it became clear how the peripheries and, therefore, the subaltern discourses, were displaced. Thus, the role that tourist areas such as Torremolinos, already since the sixties, had as a destination for the international LGBT community in the context of Franco's dictatorship and the emergence of LGBT activism during the democratic transition, remained in the background. Proof of this was the opening of what is considered the first gay bar in Spain, Tony's bar, in 1962. During almost all that decade and coinciding with the developmentalist economic policies, Torremolinos became the destination of the national and international LGBT community, in what was a kind of island in the context of the Franco dictatorship.
Keywords: Transexualismo - Historia; Identidad sexual - Investigación; Transexualismo - Torremolinos (Málaga); Movimientos sociales - España; Personas trangénero; España - Historia - 1939-1975; Queer History; Queer studies; Cruising Torremolinos; LGBT History